Dig your heels in : navigate corporate bs and build the company you deserve - Kuhl, Joan Snyder (Berrett-Koehler Publishers, 2019)
"Sought-after speaker and consultant Joan Kuhl arms young women with the tools they need to transform male-dominated corporate cultures from the inside and create the careers and work environments they want and deserve. Women can't allow a biased, male-dominated corporate culture to force them out of a company they've chosen to work for. Dig Your Heels In is a playbook that empowers women to win at the corporate achievement game and be catalysts for positive change. Joan Kuhl helps women create a clear vision of what their career path should be and make a convincing business case for equity to their managers and senior leadership. You'll learn strategies for overcoming sexist cultural attitudes about gender and leadership, as well as for dealing with self-limiting behaviors like Imposter's Syndrome (the feeling you're never good enough despite a track record of success) and the Myth of Meritocracy (the idea that just doing good work is the way to advance). Because relationships are absolutely crucial, Kuhl describes how to build support networks before you even need them and explains how to get actionable feedback that will help you get to the next level--the kind women rarely are afforded. Case studies, practical exercises, and inspiring stories from Kuhl's work with clients at companies such as Eli Lilly, Goldman Sachs, U.S. Soccer, BlackRock, Delta Airlines, and more make this a truly comprehensive guide. It's an indispensable resource for women seeking to build the confidence and conviction to secure the seat at the table they've earned and create a welcoming workplace for everyone"--